Control of Microstructure during Solidification & Homogenization of Thin-Slab Cast Direct-Rolling (TSCDR) Microalloyed Steels - Zhou, Tihe (My University, 2010)
The advantages of Thin-Slab Cast Direct-Rolling (TSCDR) process include reduced capital, energy, labour and inventory costs, as well as the ability to roll thinner strip compared to the conventional process of thick slab casting, reheating and hot rolling. There is great interest in utilizing this technology to produce microalloyed steels which can meet American Petroleum Institute (API) standards. However, whereas the conventional approach can produce APIX80, APIXlOO, and even APIX120 steels; the TSCDR process can only produce APIX70 and APIX80. The main obstacles in the way of achieving high API grades are the non-uniform initial as-cast microstructure and the large grains that result from grain growth at high temperature. The production of APIX80 and higher grade steels can only be achieved through a comprehensive research initiative that combines careful control of solidification, homogenization, thermomechanical-processing, cooling and coiling.
This contribution examines the solid state microstructure evolution of microalloyed steels under simulated TSCDR conditions. The grain growth kinetics in delta-ferrite and austenite were studied separately using two model alloys. At high temperatures and in the absence of precipitation, the growth kinetics in both delta-ferrite and austenite appeared to follow a simple parabolic growth law. The measured grain growth kinetics was then applied to the problem of grain-size control during the process of TSCDR. Several strategies of controlling and refining the grain size were examined. The kinetics of delta-ferrite to austenite phase transformation was investigated using a quenching dilatometer; the results showed that the austenite phase formed along the original delta grain boundaries, and that the precipitation of austenite at the delta-ferrite grain boundaries effectively pins delta grain growth. The kinetics of the phase transformation was modeled using a local equilibrium model that captures the partitioning of the substitutional elements during the transformation.
A novel delta-ferrite/austenite duplex microstructure is proposed to achieve fine and uniform high-temperature microstructure. The grain growth of the matrix phase (delta-ferrite) is controlled by the coarsening mechanism of pinning phase (austenite). The effectiveness of this delta/austenite duplex microstructure was validated experimentally and analyzed in details using a physically-based model.
Keywords: Microstructure; Solidification; Homogenization; Thin-Slab Cast Direct-Rolling; Microalloyed Steels